Pemilihan Presiden Amerika terhadap Saham Jakarta Islamic Index - Lukman Jensen (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2018)
This study aims to analyze and examine the impact of the Election of the Presidents of the United States with the result of Donald Trump as the American President on November 8, 2016 against the abnormal return and trading volume activity of issuer's shares listed in the Jakarta Islamic Index. Using a sample of 30 companies registered in Jakarta Islamic Index for 7 days before and 7 days after the election of the American President. The result of this study concludes that the Indonesian capital market reaction to the events of the 2016 US Presidential Election was momentary and non-prolonged. It was shown that there was no statistically significant difference between the average stock of abnormal return in the period before and after the event to the Jakarta Islamic Index. In fact, the Indonesian Capital Market responded to information of the American Presidential Election as good news as indicated by the emergence of a significant positive Trading Volume activity around the date of the event.